The impact of audience avatar movements on presence in virtual live events - Guang, Yang; Sakurai, Sho; Matsumura, Kohei; Okafuji, Yuki (Frontiers in Virtual Reality, 2025)
IntroductionVirtual live (VL) events allow audiences to participate as avatars in immersive environments, but uniform and repetitive audience avatar motions can limit emotional engagement and presence. This pilot study investigates whether varying proportions of user-controlled versus dummy (scripted) avatars affect perceived presence and synchrony.MethodsSeven participants experienced a VR concert under three conditions (0%, 50%, 100% user-controlled avatars) using the Oculus Quest 2. Presence was measured using the Igroup Presence Questionnaire (IPQ), and avatar-movement synchrony was evaluated using autocorrelation and cross-correlation analyses. A Synchronization Index (SI) was defined as cross-correlation between each participant’s motion and the group-averaged motion.ResultsPresence scores increased with a higher proportion of user-controlled avatars. SI also tended to increase in the 100% condition. Although correlations between SI and presence were moderate (r = .42) and did not reach statistical significance due to the pilot sample size, both subjective and objective trends supported the hypothesized direction.DiscussionUser-controlled audience avatars enhanced presence compared to scripted avatars, suggesting movement diversity contributes to immersive VL experiences. This study demonstrates a feasible evaluation pipeline for avatar synchrony and highlights design implications for VR live events. Future work will expand sample size, incorporate additional behavior modalities, and refine synchrony metrics.